Analisis Faktor – Faktor yang Mempengaruhi Utang Luar Negeri di Indonesia Tahun 2015-2019 - Hana Cahyaningrum; Ghalbyna Nadzeva; Novia Tri Ramadhani; Dian Hakip Nurdiansyah (Universitas Warmadewa, 2022)
The purpose of this study is to clarify the impact of exports, gross domestic product (GDP) and the rupiah exchange rate (exchange rate) on Indonesia's foreign debt. The data used in this study uses secondary data, including time series data from 2015 to 2019. The analytical tool used in this study is multiple linear regression analysis using SPSS23. The results showed that exports, gross domestic product (GDP) and the rupiah exchange rate (exchange rate) had a significant positive effect on Indonesia's external debt.